Cost efficiency, Morishima, Allen-Uzawa and cross-price elasticities among Irish potato farmers in Dedza District, Malawi - Assa, M.M.; Edriss, A.K.; Matchaya, Greenwell C. (2013)
Malawi has experienced a forward shift in its demand for Irish potato (Solanum tuberosum) consumption. Given limited resources at farmers' disposal, meeting the growing demand will require farmers to follow the efficient path of the farm production resources. This paper, therefore, is an attempt to measure the cost efficiency of smallholder Irish potato farmers in Dedza district of Malawi using a translog cost function, inefficiency effect model and input elasticities derived from a system of cost share equations estimated by Iterated Seeming Unrelated Regression method. A multi-stage random sampling technique was used to select 200 Irish potato farmers in Dedza in 2011 from whom input-output data and their prices were obtained. Results indicate that the mean cost efficiency of Irish potato production in Dedza District is 0.67 with scores ranging between 0.15 and 0.94. The cost efficiency differences are significantly explained by non-farm employment, education, credit access, farm experience, degree of specialization, household size and frequency of weeding. The highest input substitution existed between labour and fertilizer, followed by seed-fertilizer. One policy issue is raised; credit should be extended to Irish potato farmers to enable them purchase farm inputs.